On the Compactness of Fractional Resolvent Operator Functions - Lizama-Yanez, C (Springer New York LLC, 2016)
We study and characterize the compactness of resolvent families of operators associated to fractional differential equations. We show an application in the study of existence of mild solutions for a class of semilinear fractional differential equations with non-local initial conditions. © 2016, Springer Science+Business Media New York.